Complete mitochondrial genome of Prionailurus bengalensis (Carnivora: Felidae), a protected species in China - Zhang, Jian-Jun (Mitochondrial DNA B Resour, 2019)
The complete mitochondrial genome (mitogenome) of the leopard cat Prionailurus bengalensis in China was sequenced using the shotgun genome-skimming method. The mitogenome of P. bengalensis is totally 17,006 bp in length with a higher A + T content of 60.4% than that of G + C and consists of 13 protein-coding genes (PCGs), two rRNAs, 22 tRNAs, and one non-coding control region. All the PCGs initiate with a typical ATN codon and terminate with a TAA codon except for the four PCGs (COX1, ND2, ND3, and ND4) terminating with a single T—and one gene CYT B with AGA as stop codon. Most of the tRNA genes have a clover-leaf secondary structure except for tRNAS (AGN), which loses a dihydrouridine (DHU) arm. The ML phylogenetic tree showed that P. viverrinus nested in the group of P. bengalensis individuals, which is close to the clade clustered by the two genera Otocolobus and Felis.